The Geographic Information System of Gas Station (SPBU) Location In Musirawas, Lubuklinggau, and North Musirawas Based on Mobile Web - Joni Karman; Oskar Al Amin (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Making a Geographical Information System for the Location of Public Fuel Filling Stations (SPBU) in Musirawas, Lubuklinggau, and North Musirawas based on Mobile Web, the community, still has difficulty in finding the location for gas stations, especially people outside the region who also do not know the mileage so that they have the potential to run out of fuel and the community also does not know the types of fuel available at the gas station so that you have the potential to get lost when looking for a gas station location. This research uses data collection methods, by observing and recording directly at the research site (observation), conducting a direct question and answer with the resource (interview) and documentation by reading existing books and literature. The results of the geographic information system design for the location of gas station stations (SPBU) in Musirawas, Lubuklinggau, and North Musirawas based on Web Mobile was made by using the PHP programming language and MySQL database and making program listings using the Adobe Dreamweaver application. The system created by this user can select the closest gas station menu directly by pressing the button where the nearest gas station is located so that the closest gas station location where you are will appear. Information on gas stations can also be known with information which is located according to the location of the gas stations chosen, and users can provide feedback in the form of comments or suggestions for improvements to the gas stations.